Determinants in competition between cross-sector alliances - Stephen Fox; Janne Kauttio; Yusuf Mubarak; Hannu Niemisto (Administrative Sciences, 2017)
Private, public, and not-for-profit organizations come together in cross-sector alliance projects and programmes (CSA) to bring about large-scale changes. CSA can often face determined competition from other alliances that oppose large-scale change or propose alterative large-scale changes. Competition can be related to people's deeply held beliefs arising from their ideologies, cultures, and/or other sources of entrenched preconceptions. In previous CSA research, there has been little consideration of competition between CSA involving people's deeply held beliefs. Accordingly, in this paper, a conceptual framework for better understanding CSA competition is introduced. This encompasses the influence of people's beliefs and related underlying determinants. This is necessary because there are many large-scale challenges that involve private, public, and not-for-profit organizations working together in projects and programmes against competition.
Keywords: 350; beliefs; Brexit; cross-sector alliances (CSA); competition; predictive evaluations